Effectiveness of tigecycline in the treatment of infections caused by carbapenem‐resistant gram‐negative bacteria in pediatric liver transplant recipients: A retrospective study. Issue 1 (1st November 2019) - Chen, Fang; Shen, Chuan; Pang, Xiaoyun; Zhang, Zaili; Deng, Yuxiao; Han, Longzhi; Chen, Xiaosong; Zhang, Jianjun; Xia, Qiang; Qian, Yongbing
Abstract: Introduction: Tigecycline (TGC) is effective for the infections caused by carbapenem‐resistant gram‐negative bacteria (CRGNB) in adults, but it is not investigated systematically in children because of concern about adverse effects. This study aimed to analyze the effectiveness of TGC in treating CRGNB infections in children after receiving liver transplant. Methods: The subjects in this retrospective study were pediatric liver transplant recipients treated with TGC for at least 3 days to fight microbiologically verified CRGNB infection after initial antibiotic failure during the period from January 2014 to May 2018. Clinical and microbiological outcomes were reviewed to evaluate the efficacy and safety of TGC. Results: Of the 1177 pediatric liver transplant recipients, 13 patients were eligible for inclusion in this analysis. All the patients received TGC at dose of 2 mg/kg every 12 hours for a duration of 10.1 ± 5.1 days on average to treat CRGNB infections, including complicated intra‐abdominal infection, ventilator‐associated pneumonia, and bloodstream infection. The isolates included Klebsiella pneumoniae (69.2%, 9/13) and Acinetobacter baumannii (30.8%, 4/13). Clinical efficacy was achieved in 84.6% (11/13) and pathogen eradicated in 69.2% (9/13) of the patients. The overall mortality rate was 15.4% (2/13). No TGC‐related serious adverse event was reported. Conclusion: Tigecycline can be considered in combination antimicrobial regimen for treating CRGNB‐related infections in pediatric liver transplant recipients.